Comparison of fibrous catalysts and monolithic catalysts for catalytic methane partial oxidation. (August 2019) - Ma, Yuyao; Ma, Yuxia; Zhao, Zhibo; Hu, Xun; Ye, Zhengmao; Yao, Jianfeng; Buckley, C.E.; Dong, Dehua
Abstract: Fibrous Ni/Al2 O3 catalysts prepared by one-step electrospinning have been recently developed for methane reforming. The purpose of this study is to investigate the merits of the fibrous catalysts via comparing with conventional monolithic Ni/Al2 O3 catalysts prepared by impregnation. The fibrous catalysts exhibited the smaller and more uniform Ni nanoparticles, the stronger catalyst/support interaction and the higher catalyst loadings compared with supported spherical catalysts. In addition, fibrous catalysts demonstrate the faster mass transfer and the higher resistance to carbon deposition during methane partial oxidation, resulting in the higher syngas yields. Therefore, the fibrous catalysts have the advantages of the higher catalyst loading with the higher dispersion and the faster mass transfer for achieving the higher catalytic reaction rates over conventional impregnated catalysts. Graphical abstract: Image 105814 Highlights: New fibrous catalysts were compared with monolithic catalysts for methane reforming. Fibrous Ni/Al2 O3 catalysts were prepared by one-step electrospinning. Fibrous catalysts show high Ni dispersion and the strong interaction with support. Fibrous catalysts exhibit fast mass transfer and generate high syngas yields.